Eksplorasi Kreatif dalam Penciptaan Musik Instrumental Gitar: Studi Karya "Kidung Gitar" - Munggaran, Agung Riwayat (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Instrumental music is an art form that relies on the power of sound as the primary medium for conveying messages without the use of vocal elements. This study examines the creative process, foundations of creation, and musical analysis of the work "Kidung Gitar," composed by Agung Sejarah Munggaran as part of the final exam for his Music Composition course. This work combines rock, metal, and shoegaze genres, with the guitar as the primary instrument and the flute as a melodic backing. Through exploration of guitar playing techniques, the selection of popular notation, and the incorporation of conventional instruments, the composer strives to create music that communicates without words. The results of the study indicate that this work represents a fusion of technique, creativity, and a deep understanding of music theory, thus providing a unique and engaging musical experience for listeners.